2019
DOI: 10.1038/s41556-019-0314-5
|View full text |Cite
|
Sign up to set email alerts
|

U2AF1 mutations induce oncogenic IRAK4 isoforms and activate innate immune pathways in myeloid malignancies

Abstract: Spliceosome mutations are common in MDS and AML, yet the oncogenic changes due to these mutations have not been identified. A global analysis of exon usage in AML samples revealed distinct molecular subsets containing alternative spliced isoforms of inflammatory and immune genes. IRAK4 was the dominant alternatively spliced isoform in MDS/AML and is characterized by a longer isoform that retains exon 4, encoding a protein, IRAK4-Long (L) that assembles with the Myddosome, results in maximal activation of NF-κB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
170
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(177 citation statements)
references
References 57 publications
5
170
0
2
Order By: Relevance
“…In contrast to gene sets identified from our differential isoform usage analysis, we found that differentially expressed isoforms belonged to genes regulated by NF-kB via TNF signaling, most of which are downregulated (corrected p-value <0.05; Supplemental Table 6). This observation is particularly important given recent reports implicating U2AF1 S34F in altering immune-related genes (Palangat et al, 2019;Smith et al, 2019). We further examined FLAIR isoforms derived from genes in the NF-kB pathway to determine if any U2AF1 S34F-associated splicing alterations could explain expression changes.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…In contrast to gene sets identified from our differential isoform usage analysis, we found that differentially expressed isoforms belonged to genes regulated by NF-kB via TNF signaling, most of which are downregulated (corrected p-value <0.05; Supplemental Table 6). This observation is particularly important given recent reports implicating U2AF1 S34F in altering immune-related genes (Palangat et al, 2019;Smith et al, 2019). We further examined FLAIR isoforms derived from genes in the NF-kB pathway to determine if any U2AF1 S34F-associated splicing alterations could explain expression changes.…”
Section: Resultsmentioning
confidence: 98%
“…In ADC, the most recurrent U2AF1 mutation occurs at amino acid residue 34, in which a C>T transition causes a change from serine to phenylalanine (S34F). The impact of U2AF1 S34F on pre-mRNA splicing has been widely studied (Przychodzen et al, 2013;Brooks et al, 2014;Coulon et al, 2014;Ilagan et al, 2015;Shirai et al, 2015;Park et al, 2016;Yip et al, 2017;Palangat et al, 2019;Smith et al, 2019), and previous work has shown that mutant U2AF1 has an altered binding affinity with its pre-mRNA substrate (Okeyo-Owuor et al, 2015;Fei et al, 2016). In ADC, mutant U2AF1 has been shown to alter pre-mRNA splicing and other posttranscriptional processes (Brooks et al, 2014;Fei et al, 2016;Park et al, 2016;Palangat et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mutation is heterozygous, occurs early in disease progression, and is a hotspot mutation in the RNA binding domain of the protein, strongly suggesting a gain of function, oncogenic mutation. While several groups have examined alternative splicing alterations that are mediated by the S34F mutation (Brooks et al, 2014;Fei et al, 2016;Smith et al, 2019;Yoshida et al, 2011), there is no clear set of splicing events that can explain the tumorigenic role of the S34F mutation. Previously, we reported that U2AF1, in complex with U2AF2, plays a noncanonical role in translation regulation through direct interactions with target RNA in the cytosol (Palangat et al, 2019).…”
Section: Introductionmentioning
confidence: 99%